JAK KORZYSTAĆ Z KIEROWNICTWA DUCHOWEGO? (ROZWAŻANIA NA KANWIE MYŚLI FRANCISCO FERNANDEZA-CARVAJALA) - Puczyłowski, Krzysztof (Civitas et Lex, 2017)
This article explains what is spiritual leadership and provides instructions on how to use it. Spiritual life is showed as climbing on a mountain trail, with the help of an experienced guide. This help is absolutely necessary for one who is led, because the achievement of holiness resulting from and based on one’s own strength is practically impossible.